Death of guppy fish (Poecilia reticulata) leukocytes induced by in vivo exposure to temephos and spinosad. Issue 4 (3rd April 2022) - Díaz-Resendiz, K. J. G.; Hermosillo-Escobedo, A. T.; Ventura-Ramón, G. H.; Toledo-Ibarra, G. A.; Girón-Pérez, D. A.; Bueno-Durán, A. Y.; Girón-Pérez, M. I.
ABSTRACT: Temephos and spinosad are pesticides used for control of vector-borne diseases such as dengue, chikungunya and zika. However, the inadequate use of these substances has affected the health of non-target organisms. The aim of this study was to evaluate and compare, the effects of temephos and spinosad on leukocyte viability and death, using guppy fish ( Poecilia reticulate) as a model organism. Guppies were exposed to temephos (10 mg/L) and spinosad (0.5 mg/L) for 7, 14, and 21 days. Afterwards, they were placed in pesticide-free fish tanks (7, 35, and 70 days) for recovery. The results showed that exposure to temephos caused leukocyte death, even at 35 days of recovery. Contrarily, the exposure to spinosad did not cause leukocyte death. This research show, for the first time, that a single dose of temephos causes apoptosis up to 56 days post-exposition, indicating that this pesticide induces chronic effects on immune response cells.